A compact angularly‐stable frequency selective surface for GSM 900/1800‐MHz shielding using cascaded 2.5‐dimension structure. Issue 6 (31st December 2018) - Xu, Xiao‐Ming
Abstract: In this article, a novel compact dual‐band frequency selective surface (FSS) with stable response is proposed for GSM shielding. This FSS is designed using 2‐layer cascaded 2.5‐dimension structure of which element is composed of two via‐based modified swastika unit cells. The proposed structure has created two stop bands around frequency 900 and 1800 MHz, respectively, with maximum attenuation value close to 70 dB. Besides, this FSS performs an excellent miniaturization characteristic with overall size of 0.048 λ 0 × 0.048 λ 0, where the λ 0 represents the free space wavelength of the lower resonance frequency. More important, this FSS exhibits a very stable frequency response up to 80° for TE and TM polarization. To understand the structure better, the design procedure of this FSS is introduced in detail. Since the proposed FSS has an excellent comprehensive performance, this FSS has great potential in shielding GSM signal for small electronic devices. Finally, a prototype of proposed FSS is fabricated and measured. The measurement results prove the validity of simulation results.